The analytic use of rubrics in writing classes by language students in an EFL context: students’ writing model and benefits - Bin Dahmash, Nada Fahad (Frontiers in Education, 2025)
PurposeThis study examines the process of using analytic rubrics in higher education, focusing on students in a writing course for basic users of English, the resources they employ as they use the rubric, and the benefits they perceive from it.MethodThe study involved 13 students (N = 13) enrolled in a basic English writing course. After completing the course, semi-structured interviews and stimulated recall sessions were conducted with participants. The focus was on understanding their use of the analytic rubric in their writing process and the resources they utilized, such as smartphone apps, the Grammarly website, and both mobile and desktop versions of MS Word.FindingsThe results indicated that the students exhibited a writing model, comprising recursive and tangled five steps. Long-term benefits included improved self-efficacy, writing skills, satisfaction, and task-management skills. In the short-term, the rubric helped clarify the requirements, served as a benchmark for their writing, and highlighted their strengths and weaknesses in the writing process.OriginalityThis study contributes to the limited research on the use of analytic rubrics in EFL contexts in higher education, providing insights into the writing process of basic English learners and the benefits of rubric use in language learning.